2005
DOI: 10.5014/ajot.59.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care at School: Perceptions of 6-Year-Old Children

Abstract: Occupational therapists who work with young children routinely evaluate self-care and consider it an important domain of practice. Little is known about what children perceive is important self-care or what they experience as self-care within a school context. Without knowledge about children's perspectives of self-care, occupational therapists cannot know whether or not they are targeting areas that are central to children's needs. The purpose of this naturalistic study was to explore 6-year-old children's pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
2
12
0
1
Order By: Relevance
“…Next, the children were asked to make a drawing about something they felt was related to their asthma. The moderator used the drawings for the facilitation of the discussion during the first session [ 18 , 19 ]. In the second session, the discussion was facilitated by a fishing rod game with visual cues of the five domains of HRQL to introduce different dimensions of HRQL [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the children were asked to make a drawing about something they felt was related to their asthma. The moderator used the drawings for the facilitation of the discussion during the first session [ 18 , 19 ]. In the second session, the discussion was facilitated by a fishing rod game with visual cues of the five domains of HRQL to introduce different dimensions of HRQL [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The moderator used the drawings for the facilitation of the discussion during the first session [ 18 , 19 ]. In the second session, the discussion was facilitated by a fishing rod game with visual cues of the five domains of HRQL to introduce different dimensions of HRQL [ 19 ]. Based on domain cards that were fished out by the children, children were asked to think about HRQL issues that were related to these domains.…”
Section: Methodsmentioning
confidence: 99%
“…These skills are achieved as the child develops the ability to: (a) isolate finger movements which is required for in‐hand manipulation and for tool use, (b) to use the thumb and two radial fingers actively for grasp, for example, in holding a pencil or using scissors or managing fasteners, while the ulnar side of the hand and the wrist is stable, (c) use both hands cooperatively, for example, in managing buttons, zips, shoe laces and other fastenings, scissor use and in writing. School‐aged children are expected to tie their own shoelaces, manage food packaging and dress – all tasks requiring a range of fine motor skills (Chapparo & Hooper, ; Sigelman & Rider, ). In previous studies, motor coordination/visual motor integration and dexterity have been identified as being critical when learning to copy letters (Volman, van Schendel & Jongmans, ) and to handwriting performance (Case‐Smith, ; Cornhill & Case‐Smith; Dankert, Davies & Gavin, ).…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining a card, each child was invited to answer the question on the card either directly, through story telling of specific instances at school and home or by acting out a response. This methodology has been successful in previous research that sought to obtain young children's perceptions of others at school (Chapparo & Hooper, ). The second part of the group interview involved role‐play.…”
Section: Methodsmentioning
confidence: 99%